Determinants Of Fraudulent Financial Statement On Islamic Banks In The Perspective Of Crowe’s Fraud Pentagon Theory - Aminatun, Siti; Mukhibad, Hasan (Universitas Gorontalo, 2021)
This study aims. to.analyze the determinants of. Fraudulent. financial statements. such us external pressure, financial target, effective monitoring, external auditor quality, Profit Sharing Ratio, Director’s Employee Welfare Ratio, Non Islamic Income Ratio, change in director, dan CEO Duality in thee perspective crowe’s fraud pentagon. theory on Islamic Banking in Indonesia during 2015-2019. The sampling. method used was purposive. sampling and generated 62 units of analysis. The results show that Profit Sharing Ratio has a negative effect and Non Islamic Income Ratio have positive effect on fraudulent financial statements. Meanwhile the external pressure, financial targets, effective monitoring, external auditor quality, change in directors and CEO duality have no effect on fraudulent financial statements.